Analysis and Design of a Passively Damping LCL Filter in Three-Phase Converters - Xavier, TADOUMGANG Francois; Wenping, QIN (International Journal of Advanced Engineering Research and Science, 2019)
This article discusses the mitigation of high-frequency harmonics through high voltage converters. First we present a generalized model of the passively cushioned LCL filter and then, the optimization process is implemented, which results in the low consumption of active and reactive energy of the capacitor resistance branch. The output characteristics of the passively amortized LCL filter are determined by three parameters of different combinations with the same output result: total L induction, the damping ratio and natural frequency. In a second time we present the design of a control line of the LCL filter on the referential theory giving rise to a simpler way the calculation of different characteristics or combinations such as peak resonance, impedance as well as certain elements that consume reactive and active energy from the RC branch of our LCL filter. The simulations were performed in the Matlab/Simulink environment. The results show a significant improvement in the harmonic attenuation rate.